2015
DOI: 10.1155/2015/601970
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of NiO and NiCl2 Hydrogen Reduction as Precursors and Properties of Produced Ni/Al2O3 and Ni‐Pd/Al2O3 Catalysts

Abstract: The objects of this investigation were the comparative kinetic analysis of the NiO and NiCl2 reduction by hydrogen during an induction period and elimination of the calcination during the synthesis of Ni/Al2O3 catalysts. The effect of temperature and time on NiO and NiCl2 reduction degrees was studied. Avrami I equation was selected as the most favorable kinetic model and used to determine activation energy of the NiO and NiCl2 reduction for the investigated temperature range (623–923 K) and time intervals (1–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…However, due to the limited stability of Au@SiO 2 at high temperatures and the practical limitations of the Linkam Cell brought about by the high heat capacity of H 2 , the maximum temperature that can be reliably achieved is 400 °C. For the precursor samples we have chosen to eliminate a calcination step as the reduction of nickel oxide occurs at even higher temperatures than the direct reduction of the herein used Ni precursors …”
Section: Resultsmentioning
confidence: 95%
“…However, due to the limited stability of Au@SiO 2 at high temperatures and the practical limitations of the Linkam Cell brought about by the high heat capacity of H 2 , the maximum temperature that can be reliably achieved is 400 °C. For the precursor samples we have chosen to eliminate a calcination step as the reduction of nickel oxide occurs at even higher temperatures than the direct reduction of the herein used Ni precursors …”
Section: Resultsmentioning
confidence: 95%
“…Utilization of chlorides instead of oxide precursors that are obtained by calcination can enable lower energy consumption because the calcination is avoided during the production of Ni-based catalysts [16]. Moreover, kinetic analysis of NiO and NiCl 2 hydrogen reduction confirmed that the oxide phase is more stable and less reducible than the chloride phase [18].…”
Section: Fig 2 Ni-pd/al 2 O 3 Reduced At 533 K Metal Loading (Wt mentioning
confidence: 99%
“…Chloride precursors for metals were almost completely reduced by hydrogen at 533 K. Utilization of chlorides instead of oxides in the production of catalysts can provide energy savings due to elimination of the calcination [16]. In addition, chlorides have higher reducibility than oxides obtained by calcination [18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite obtaining high-performance catalysts, thermo-chemical synthesis routes are complex from a cost-effective point of view: they last from 30 to 50 hours or even up to a few days and require large amounts of complex chemical composition solutions [2,[4][5][6][7][8][9][10]. Hence, it is highly desirable to simplify the catalyst production processes by reducing the number of process stages and in conjunction also achieve a lower environmental impact when compared with the thermo-chemical synthesis routes [11][12][13].…”
Section: Introductionmentioning
confidence: 99%